Pembiasaan Nilai-Nilai Keislaman Dalam Lingkungan Kampus dan Ma’had UIN Maulana Malik Ibrahim Malang - Hafidzulloh, Muhammad (Maliki Interdisciplinary Journal, 2026)
This study aims to describe the process of habituation of Islamic values ​​in the Campus and Ma'had environment of UIN Maulana Malik Ibrahim Malang and its impact on the formation of student character. This study uses a qualitative approach with descriptive research. Data were obtained through observation, documentation, and literature studies related to the Islamic development program in the campus environment and Ma'had Sunan Ampel Al-Aly. The results of this study indicate that the habituation of Islamic values ​​at UIN Maulana Malik Ibrahim Malang is implemented in an integrated manner through institutional policies, religious academic culture, and a pesantren-based development system. Ma'had programs, religious activities, and the exemplary behavior of the academic community are the main means of internalizing Islamic values ​​to students. This habituation has a positive impact on the formation of student character, especially in fostering noble morals, disciplined worship, responsibility, social concern, and spiritual awareness. The synergy between the campus and Ma'had Sunan Ampel Al-Aly plays an important role in creating students who are not only academically superior, but also have a strong Islamic identity in accordance with the concept of Ulul Albab.